Localised, advanced prostate cancer: combined hormonal treatment and radiotherapy - Stryczyńska, Grażyna; Milecki, Piotr; Nawrocki, Sergiusz; Stachowski, Tomasz; Kwias, Zbigniew (Contemporary Oncology/Współczesna Onkologia, 2001)
In this paper various options of hormonal treatment are summarised. Prostate cancer is a perfect example of a hormone-dependent malignancy. Androgens maintain balance between proliferating and dying epithelial cells in the prostate, whereas they are growth factors for the transformed malignant cells. Testosterone is a critical factor in initiation and progression of prostate cancer. Based on the early studies carried by Huggiens and coworkers, it has been known that the male hormones promote the growth of both the prostate gland and cancer cells. Surgery is not an effective treatment in advanced T3 tumours and hormone therapy combined with the modern-era conformal radiotherapy (3 D – CRT) seems to be a very attractive treatment option for localised and especially for locally advanced prostate cancer. However, there are still many unresolved issues which are discussed in this paper: what is optimal timing of hormonal treatment and radiotherapy, when hormonal treatment should be initiated an for how long should bc continued? The idea that addition of androgen ablation therapy to radiotherapy could improve the results of combined treatment was based on earlier experience with application of neoadjuvant hormonal therapy with surgery. One of the first trial, which indicated increase the disease-free survival, but without prolongation of the overall survival, probably due to a large amount of intercurrent diseases was the trial conducted by the Andersen Cancer Centre in Houston. In this trial conducted in pre PSA era the combined treatment (diethylostylbestrol plus radiotherapy) versus radiotherapy alone was compared. Recent results of clinical trials demonstrated the therapeutic benefit of both neoadjuvant and adjuvant hormonal treatment combined with radiotherapy vs. radiotherapy alone. The trial RTOG 86-10 was the first clinical trial which evaluated a role of neoadjuvant androgen deprivation (goserelin plus flutamide) with radiotherapy. In this trial in the experimental arm neoadjuvant (2 months) and than during radiotherapy androgen ablation was performed. In conclusion of this trial the combined treatment provided better results of treatment. Another example of randomized trial evaluated results of combined treatment was the trial conducted by Bolla et coworkers. This trial indicated that the therapeutic gain due to long-term adjuvant androgen deprivation compared to radiotherapy alone. It is worth to note that adjuvant hormonal therapy was continued in investigated arm for 3 years. Results of this trial indicated that the 5-year overall survival in combined treatment arm was 79% vs. 62% in radiotherapy alone group, respectively. In another major study reported by Laverdiere at al. was indicated that combined treatment (androgen blockade plus radiotherapy) was connected with better outcomes of treatment. The last published data based on results of the trial RTOG 9202 once again indicated that combined treatment caused decrease in failures of treatment. In this trial 1554 patients were entered and according to the trial’s protocol all patients received of gosorelin and culexin 2 months before and than during radiotherapy. After completion of radiotherapy were randomized to no further therapy or 24 months of additional goserelin alone. In conclusion of this trial in investigated arm improvement in the biochemical control (46% vs. 21%) was showed. In summary, data from many trials indicated that in group of patients with higher risk of disease failure the longer hormonal treatment may caused a better results of combined modality. On the other hand, prolonged androgen deprivation may produce some decrease in patient’s quality of life due to loss of sexual potency.